1999
DOI: 10.1046/j.1523-1747.1999.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38 Mitogen-Activated Protein Kinase and Caspases in UVB-Induced Apoptosis of Human Keratinocyte HaCaT Cells

Abstract: Exposure of human keratinocyte HaCaT cells to ultraviolet B-irradiation induced apoptotic morphologic changes. In this study, we found that the ultraviolet B irradiation (0.25 J per cm2) induced phosphorylation of p38 mitogen-activated protein kinase and c-jun N-terminal protein kinase, and also significant activation of caspase-3 (CPP32-like protease) and a small increase of caspase-1 (ICE-like protease) activity in the early stages of ultraviolet B-induced apoptosis. Pretreatments of the cells with a p38 mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
1
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 27 publications
12
93
1
4
Order By: Relevance
“…Our study demonstrated that UVB irradiation-induced apoptosis of SVHK cells is accompanied by a delayed phosphorylation of p38 and JNK with similar time courses. The results are in line with the previous reports showing that UV mediated apoptosis is associated with the activation of JNK in immortalized mouse keratinocyte cell line, C50 [33] and in HaCaT cells [17].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study demonstrated that UVB irradiation-induced apoptosis of SVHK cells is accompanied by a delayed phosphorylation of p38 and JNK with similar time courses. The results are in line with the previous reports showing that UV mediated apoptosis is associated with the activation of JNK in immortalized mouse keratinocyte cell line, C50 [33] and in HaCaT cells [17].…”
Section: Discussionsupporting
confidence: 93%
“…The In many cells including keratinocytes, UVB irradiation-induced apoptosis depends on p38 [9,17,31]. Still UVB-induced activation of ERK and JNK has been reported in normal human keratinocytes and in HaCaT cells [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach has yielded evidence for both pro-apoptotic (Bulavin et al, 1999;Shimizu et al, 1999;Zhuang et al, 2000;Gratton et al, 2001) as well as anti-apoptotic (Nemoto et al, 1998;Ivanov and Ronai, 2000) functions of these kinases. In addition, although many studies have correlated p38 activation with oxidative stress-induced apoptosis, in some of these circumstances, inhibiting the kinase through use of pharmacologic inhibitors does not alter the apoptosis (Wang et al, , 2000a.…”
Section: Sapk Pathwaysmentioning
confidence: 99%
“…For example, p38 elicits a pro-apoptotic signal in response to UV-B irradiation of human keratinocytes through upregulation of caspases (Shimizu et al, 1999). This signal can be attenuated by the PI3K/AKT pathway (Berra et al, 1998).…”
Section: Introductionmentioning
confidence: 99%